(untitled) (World Bulletin of Public Health, 2024)
The landscape of elementary education is rapidly evolving due to technological advances, changes in pedagogical practices, and an increasing focus on personalized learning. This research paper examines contemporary approaches to elementary education, focusing on innovative strategies such as personalized learning, inclusive practices, STEAM education, and digital literacy. By reviewing these approaches, this article aims to illuminate how educators can adapt to meet the diverse needs of today’s students and create a dynamic and engaging learning environment